2019
DOI: 10.1038/s41380-019-0611-1
|View full text |Cite
|
Sign up to set email alerts
|

De novo variation in bipolar disorder

Abstract: Bipolar Disorder (BD) is a common, highly heritable disorder that affects 1-2% of the world’s population. To date, most genetic studies of BD have focused on common gene variation, and, while robustly associated loci have been identified, a substantial proportion of the heritability remains missing and could be partially attributable to rare variation. In this study, we apply a de novo paradigm in BD to identify newly arisen variants that have yet to undergo natural selection and may rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…As mentioned above, sequencing efforts in BD are currently in their infancy (Forstner et al, 2020;Goes et al, 2016;Maaser et al, 2018;Sul et al, 2020;Toma et al, 2018). Although studies Psychological Medicine provide evidence that rare variants might contribute to the etiology of BD, weak statistical power due to small sample sizes remains an issue.…”
Section: Larger Sequencing Effortsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, sequencing efforts in BD are currently in their infancy (Forstner et al, 2020;Goes et al, 2016;Maaser et al, 2018;Sul et al, 2020;Toma et al, 2018). Although studies Psychological Medicine provide evidence that rare variants might contribute to the etiology of BD, weak statistical power due to small sample sizes remains an issue.…”
Section: Larger Sequencing Effortsmentioning
confidence: 99%
“…While the cost of whole-exome sequencing (WES) and whole-genome sequencing (WGS) has decreased, these technologies are still substantially more expensive than common genotyping arrays. As a result, WGS/WES studies of BD have been limited to small studies consisting mostly of large pedigrees to potentially enrich the sample with causal rare variants and increase power (Forstner et al, 2020 ; Goes et al, 2016 , 2019 ; Maaser et al, 2018 ; Sul et al, 2020 ; Toma et al, 2018 ). While these studies have found evidence of higher rare deleterious burden in cases (Sul et al, 2020 ), higher disruptive variant burden in early-onset cases (Toma et al, 2018 ), evidence of rare variant segregation in pedigrees (Forstner et al, 2020 ; Goes et al, 2016 ; Maaser et al, 2018 ), and evidence of de novo variation (Goes et al, 2019 ), much larger sample sizes will be required to definitively identify rare variants conferring risk for BD.…”
Section: Molecular Genetic Epidemiologymentioning
confidence: 99%
“…Genome-wide association studies (GWAS) revealed that BD is a polygenic disorder caused by multiple genetic risks with small effect sizes, similar to schizophrenia (SZ), and shared genetic risks with other psychiatric disorders, such as SZ and autism 4-6 . Additionally, the contribution of de novo loss-of-function mutations, as well as de novo copy number variations, has been suggested in the etiology of BD 7-9 . Although the genetic landscape of BD is gradually becoming understood, heritability estimated from epidemiological studies is modestly accounted for by these genetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphoinositides pathway, which is hypothesised to participate in the mechanism of action of lithium, is one of the pathways for the identified variants and involved genes. 86 In 2020, Nakajima et al published the results of WGS of a proband from a family in which bipolar disorder co-segregated with a Mendelian kidney disorder. WGS detected a damaging mis-sense mutation in NTRK1 on chromosome 1q22 that encodes Tropomyosin-related kinase A (TrkA).…”
Section: Polygenicity and Polygenic Scoresmentioning
confidence: 99%
“…These variants are more linked with or play roles in the phosphoinositides pathway, calcium signalling, cholinergic neurotransmission, mitochondrial-related events, response to antipsychotic treatments, neuronal morphogenesis and microtubule polarity. 20,[81][82][83]86,87 Furthermore, several WGS studies found no high-impact rare variants or revealed no evidence of implication of specific set of risk loci or common pathways that may be used to explain the 'missing heritability' of bipolar disorder. 70,80,88 MRI neuroimaging MRI is a widely used tool for studying human brain structure and function, with the goal of establishing links, or endophenotypes, between behavioural symptoms in mental disorders and underlying pathophysiology and genomic risk.…”
Section: Polygenicity and Polygenic Scoresmentioning
confidence: 99%